2005
DOI: 10.1002/mus.20489
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and amyotrophic lateral sclerosis

Abstract: The causes of motor neuron death in amyotrophic lateral sclerosis (ALS) are still unknown. Several lines of evidence suggest that mitochondrial dysfunction may be involved in the pathogenesis of ALS. Biochemical and morphological mitochondrial abnormalities have been demonstrated in postmortem spinal cords of ALS patients. Furthermore, in transgenic mice expressing mutant Cu,Zn-superoxide dismutase (SOD1), the antioxidant enzyme associated with familial ALS (FALS), mitochondrial abnormalities precede the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 100 publications
(105 reference statements)
3
88
0
1
Order By: Relevance
“…23 Second, ALS has been increasingly linked to mitochondrial dysfunction and disturbances in bioenergetics. Mitochondrial abnormalities have been identified in postmortem tissue derived from ALS patients, 24 with ALS-linked SOD1 mutations shown to associate with mitochondria and disturb their bioenergetic capacity through an interaction with VDAC1. 25 In vivo autoradiography studies in SOD1 mice have also demonstrated that glucose utilization is impaired in motor tracts before any pathologic alterations and that this is accompanied by ATP depletion.…”
Section: Discussionmentioning
confidence: 99%
“…23 Second, ALS has been increasingly linked to mitochondrial dysfunction and disturbances in bioenergetics. Mitochondrial abnormalities have been identified in postmortem tissue derived from ALS patients, 24 with ALS-linked SOD1 mutations shown to associate with mitochondria and disturb their bioenergetic capacity through an interaction with VDAC1. 25 In vivo autoradiography studies in SOD1 mice have also demonstrated that glucose utilization is impaired in motor tracts before any pathologic alterations and that this is accompanied by ATP depletion.…”
Section: Discussionmentioning
confidence: 99%
“…G37R mice A number of lines of evidence indicate mitochondrial abnormalities in the spinal cord in ALS and in transgenic mice expressing SOD1 mutants (Wong et al, 1995;Kong and Xu, 1998;Jaarsma et al, 2000;Bendotti et al, 2001;Hervias et al, 2006). Mutant SOD1 has been shown to preferentially associate with spinal cord mitochondria via tight association or cross-linking to the outer mitochondrial membrane (Liu et al, 2004).…”
Section: Increase In Mitochondrial Iron In Sod1mentioning
confidence: 99%
“…A large body of evidence of mitochondrial abnormalities, morphologic and bioenergetic, are observed in human familial and sporadic ALS, as well as in many of the cell-culture and rodent models of SOD1-linked ALS (25,55). Like the wild-type protein, familial ALS-linked mutant SOD1 also accumulates in mitochondria, where it is thought to contribute directly to disease pathogenesis.…”
Section: Mutant Sod1 and Mitochondrial Dysfunction In Familial Alsmentioning
confidence: 99%